3D Directional Perception Using a Continuum Soft Robot: Toward a Novel Soft-Haptics Paradigm - Vazquez-Garcia, Carlos-Ernesto; Garcia-Hernandez, Nadia; Parra-Vega, Vicente; Urzua-Correa, Sergio-Edgardo; Olguin-Diaz, Ernesto (Robotics Reports, 2024)
The problem of how a soft-body 3D robot, grasped with palm-fingers, can effectively convey directional clues remains an open subject. When grasping a soft robot, the controlled stimuli involve recruitment encapsulated mechanoreceptors due to the active deformation of the soft robot, in contrast to conventional fingertip haptics that use rigid-body robots. Specifically, when a 3D continuum soft robot (cSR) is used as a haptic device, it is unclear how longitudinal, azimuthal, and curvature deformation coordinates convey actively directional haptic perception. Henceforth, an emerging topic arises, hereby identified as a novel paradigm of soft haptics in view of the guaranteed highly compliant interaction behavior of cSR. In this article, we address the question of what directional clues can be conveyed when grasping a 3D cSR probe, aimed at elucidating toward a soft haptic display. A complex cSR dynamic structure is considered, in closed loop with a known nonlinear controller, and a 10-subject user study is implemented. Findings show that 3D directional information can be achieved with high accuracy, wherein curvature stands for the dominant deformation coordinate of perception. Results offer insights into developing a soft haptic methodology, and its design principles, for an actionable and augmented user 3D cSR directional interface, where a variable stiffness method is still required to convey force cues and develop a soft-haptic interface.